Supplementation of Yeast (Saccharomyces cerevisiae) and Traditional fermentation Starter (Loog-Pang) on Nutritive Value and Kinetic of degradation of of Pineapple Peel by In vitro Gas Production Technique - Phromnoi, Siriwadee; Laorodphan, Norakamol (Journal of Mahanakorn Veterinary Medicine, 2021)
This research study investigated supplementation of Yeast (saccharomyces cerevisiae) and traditional fermentation starter (Loog-Pang) on nutritive value of and kinetic of degradation of of pineapple peel by in vitro gas production technicque. A 3x3 factorial experiment was conducted in a 3x3 factorial completely randomized design (CRD), which divided into 2 factors: 3 fermentation processes (non-microbial fermentation, fermentation with 0.04% saccharomyces cerevisiae and fermentation with 0.04% traditional fermentation starter), and fermentation time (0, 7 and 14 days). Proximate analysis was performed to determine the nutritive value, and digestibility was measured using the gas production technique. The results showed that pineapple peels fermented with traditional fermentation starter had higher crude protein than those with the other fermentation processes (P<0.01), but showed no difference in dry matter, moisture and lipid. It was found that the nutritive value started to change on the 7th day, particularly crude protein content which was significantly increased (P<0.01). The gas accumulation at different hours showed that pineapple peels fermented with yeast and traditional fermentation starter had less accumulated gas than the control group (P>0.05). The gas production from the degradable fraction (b), and the potential extent of gas production (a+b) of the pineapple peels (control group) was higher than the pineapple peels fermented with yeast and with traditional fermentation starter (P<0.01). It can be concluded that fermentation with yeast and traditional fermentation starter increased crude protein in the pineapple peels, but decreased the gas accumulation in the experiment, indicating that microbial fermentation processes potentially enhance the nutritive value of pineapple peels.